Implementation of 5S and Safety Awareness in the Classroom Environment at Telkom University Surabaya - Chandra, Huki; Ardianto, Yashmine Mela; Novika, Norma; Angeli, Febrin Claudia; Agnia, Nilna (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
The application of 5S culture is now an obligation that must be implemented by every place for the convenience of users or building occupants. The implementation of 5S that has been designed can produce an effective, efficient, productive work culture and uphold work safety. 5S culture is a culture of one of the concepts of industrial engineering. This concept is simple, easy to understand, and is the first step in the dissemination of industrial engineering culture. 5S itself is not only applied to office buildings but can also be applied to classes where various activities are carried out and also require 5S to avoid danger. There is one effective approach to increasing security awareness and ensuring a conducive work environment through implementing 5S (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). This 5S implementation provides insight into work safety around us. Data analysis by collecting data sourced from related journals and also by observing the object to be studied. Implementation of the 5S concept and safety awareness is very important, especially in classrooms on campus consisting of many people, so the risk of work accidents will be high if not balanced by the implementation of 5S and safety awareness.